Diversity Assessment of Bivalves in the Intertidal Zone in Pilar Bay - Obligar, Philomel Innocent (International Journal of Applied Research and Sustainable Sciences, 2024)
Municipality of Pilar is the last town in the eastern province of Capiz. Pilar Bay, spanning 20 square kilometers, is a boon. At low tide, a variety of edible bivalves' shells may be found around the bay's shoreline, offering a source of money for the residents. The loss in bivalve variety, abundance, and ecological functions due to overharvesting signifies a loss of environmental integrity at the local and watershed levels. The purpose of this study was to catalog and assess the variety of edible bivalves found in the Municipality's intertidal zone. Descriptive survey methods were used to gather data from December 2015 to January 2016 in eight barangays in Pilar: Dulangan, Binaobawan, Rosario, Poblacion, Natividad, San Ramon, Casanayan, Balogo, and Dayhagan. Three 1 × 1 m2 quadrats were placed down in each of the nine stations that were chosen using the belt transect approach and a quadrat. The following items were utilized to perform the study: a tiny garden trowel, a laptop computer, a nylon rope, pegs, a meter stick, and a camera. The findings indicate that seven (7) edible bivalves belonging to the families Arcidae, Veneridae, Psammobidae, Mactridea, and Solenidae were known locally as paros, litob, punaw, bug-atan, higda-higda, tikhan, and kagaykay. It also demonstrates which species were most prevalent and prolific in Pilar's intertifal zone: litob, punaw, kagaykay, higda-higda, and bug-atan.